Optimizing Heating system management using an activity-based pervasive application - Bruegger, P.; Pallotta, V.; Hirsbrunner, B. (Journal of Digital Information Management, 2009)
The greenhouse gas effect has become a major preoccupation worldwide. Heating of buildings and houses is one of the major sources of this effect. We propose to optimize heating control systems by directly integrating the recognition of people's activities and context in the process of temperature regulation. We introduce the concept of kinetic-awareness as a way of making a heating control system aware of a user's motion in physical space in order to adjust temperature according to their current activities.
Keywords: Context awareness; Heat control systems; Heating system management